Preparation and Physico-mechanics Properties of Non-sintered Ceramsite from Iron Tailing Fly Ash - Rui ZHANG; Jianguo LU; Huayan YAO; Yunze LI; Junxiong LU; Shuaiting LIU (Kuangchan zonghe liyong)
This is an article in the field of mineral materials. Non-sintered ceramsite were prepared using iron tailings and fly ash as the main raw materials, and the effects of iron tailings proportion on the stacking density, apparent density, water absorption, and strength of non-sintered ceramsite were studied at different material mix ratio. The results showed that with the increase of iron tailings proportion, the stacking and apparent density of ceramsite gradually increased, while the water absorption gradually decreased. The strength shows a trend of decreasing first and then increasing. The method of preparing ceramsite from iron tailings can significantly improve the utilization rate of iron tailings. The non-sintered ceramsite production have practical application value and can provide a new way for the comprehensive utilization of iron tailings with good economic and environmental benefits.